Gene Expression during Survival of Escherichia coli O157:H7 in Soil and Water - Duffitt, Ashley D. (Hindawi Publishing Corporation, 2011)
The in vitro survival of Escherichia coli O157:H7 at 15°C under two experimental conditions (sterile soil and sterile natural water) was examined. DNA microarrays of the entire set of E. coli O157:H7 genes were used to measure the genomic expression patterns after 14 days. Although the populations declined, some E. coli O157:H7 cells survived in sterile stream water up to 234 days and in sterile soil for up to 179 days. Cells incubated in soil microcosms for 14 days expressed genes for antibiotic resistance, biosynthesis, DNA replication and modification, metabolism, phages, transposons, plasmids, pathogenesis and virulence, antibiotic resistance, ribosomal proteins, the stress response, transcription, translation, and transport and binding proteins at significantly higher levels than cells grown in Luria broth. These results suggest that E. coli O157:H7 may develop a different phenotype during transport through the environment. Furthermore, this pathogen may become more resistant to antibiotics making subsequent infections more difficult to treat.